2015
DOI: 10.1507/endocrj.ej15-0236
|View full text |Cite
|
Sign up to set email alerts
|

Let-7 related genetic variation and risk of metabolic syndrome in a Chinese population

Abstract: MicroRNA (miRNA) related genetic variation may change miRNA binding affinity and mRNA expression levels of the target genes, thus leading to altered metabolic parameters. This study explored the influence of let-7 related single nucleotide polymorphisms (SNPs) on individual susceptibility to metabolic syndrome (MetS) in a Chinese population. Seven SNPs located at the pri-let-7 gene region, pre-let-7 gene region or 3’-UTR of the KRAS gene were selected. The SNPs were genotyped in 503 MetS patients and 529 norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Associations between variation in pri‐miRNA and diseases have been reported in multiple studies. rs10877887 TC genotype in pri‐let‐7i conferred a significantly higher risk of metabolic syndrome when compared with TT genotype (Yan et al, 2015). rs531564 GG genotype in pri‐miR‐124‐1 may upregulate the expression of miR‐124, which is a cancer suppressor and eventually decrease the risk of esophageal squamous cell carcinoma (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Associations between variation in pri‐miRNA and diseases have been reported in multiple studies. rs10877887 TC genotype in pri‐let‐7i conferred a significantly higher risk of metabolic syndrome when compared with TT genotype (Yan et al, 2015). rs531564 GG genotype in pri‐miR‐124‐1 may upregulate the expression of miR‐124, which is a cancer suppressor and eventually decrease the risk of esophageal squamous cell carcinoma (Zhang et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…16 Mutations, such as single nucleotide polymorphisms (SNPs), of miRNAs may also change miRNA and mRNA expression levels, thus leading to altered metabolic parameters. 17 On the other hand, the action of miRNA controls the translation of various messengers RNAs (mRNAs). Yan 18 found that increased levels of miRNA-18a and miR-34c can alter susceptibility to stress-related diseases by regulating GR and CRFR1 mRNA expression respectively, which…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Jiang et al reported a relatively higher let‐7d expression in cultured myotubes in T2DM subjects than that in NGT (normal glucose‐tolerant) subjects ( p = .08) (Jiang et al, ). In 2015, Yan et al reported that although there were no associations of the let‐7d rs10993081 allele in the dominant and recessive inheritance models with T2DM, the A/G genotype of rs10993081 in let‐7d was associated with an increased risk of metabolic syndromes compared with AA genotypes ( p = .006; OR = 1.42, 95% CI: 1.11–1.83) (Yan et al, ). In the current study, we also did not find that rs10993081 and rs7045890 in let‐7d were associated with T2DM.…”
Section: Discussionmentioning
confidence: 99%